Financial Literacy Mobile Application For Unimas Undergraduate Students - Liew, Zhao Ting (Universiti Malaysia Sarawak (UNIMAS), 2022)
The lack of financial literacy among university students might lead to financial difficulties such as debts. The need to improve individual thoughts on their financial literacy to have better financial management so they can implement good financial management in the future. Hence, the project intends to develop a financial literacy mobile application for UNIMAS undergraduate students to teach financial literacy. By utilizing the use of mobile application, the mobile application can teach financial literacy especially UNIMAS undergraduate students. By analyzing the literature review, three existing mobile applications were used to teach financial literacy. The mobile application provides expense tracker features as a tool to understand their financial by tracking their spendings and making wise financial decisions. In addition, usability testing will be carried out after the proposed mobile application is implemented to evaluate the usability of the mobile application by collecting feedback from user. Functional testing will be used to ensure the developed mobile application will be tested and ready for deployment. The methodology used in the proposed project is Rapid Application Development (RAD). This proposed project in Final Year Project 1 aims to design and develop to teach financial literacy and to evaluate the usability of the proposed mobile application to UNIMAS undergraduate students. Final Year Project 2 outlined the implementation and testing phase of the proposed mobile application based on the requirement analysis and system design that was defined. Furthermore, when the proposed mobile application had been deployed, functional testing such as unit testing, as well as usability testing were carried out to collect feedback from actual users. Finally, one of the proposed mobile application's limitations is that the system does not support platforms apart from Android, no multilingual support and autoscanning feature. The future work is to overcome the limitations in order to enhance the mobile application by implementing cross-platform frameworks, adding multilingualsupport and autoscanning receipt feature in the future